Home range, residency and movements of Diplodus sargus and Diplodus vulgaris in a coastal lagoon: connectivity between nursery and adult habitats - Abecasis, D. (2017)
Acoustic telemetry and standard tag-recapture were used to determine the home range and residency of juveniles and sub-adults of Diplodus sargus and Diplodus vulgaris in the Ria Formosa (Portugal) coastal lagoon. Maximum time between recaptures for the standard tag-recapture method was 128 days for D. sargus and 30 days for D. vulgaris. The majority of the fish were recaptured in the vicinity of the tagging location. Fish tagged with acoustic transmitters had a maximum period of time between first and last detections of 62 days for D. sargus and 260 days for D. vulgaris. Minimum convex polygons areas ranged between 148 024 m2 and 525 930 m2 for D. sargus and between 23786 m2 and 42134 m2 for D. vulgaris. Both species presented a high residency index between first and last detections. Two D. sargus tagged with acoustic tags were recaptured by fishermen outside the coastal lagoon at distances of 12 km and 90 km from the tagging position, providing evidence that this species leaves the Ria Formosa during the winter time for the adjacent coastal waters. The results of this study reinforce the importance of Ria Formosa as a nursery for D. sargus and D. vulgaris in the south coast of Portugal.